Geometry of the Deep Calabrian Subduction (Central Mediterranean Sea) From Wide‐Angle Seismic Data and 3‐D Gravity Modeling. (11th March 2020) - Dellong, David; Klingelhoefer, Frauke; Dannowski, Anke; Kopp, Heidrun; Murphy, Shane; Graindorge, David; Margheriti, Lucia; Moretti, Milena; Barreca, Giovanni; Scarfì, Luciano; Polonia, Alina; Gutscher, Marc‐Andre
Abstract: The Calabrian subduction zone is one of the narrowest arcs on Earth and a key area to understand the geodynamic evolution of the Mediterranean and other marginal seas. Here in the Ionian Sea, the African plate subducts beneath Eurasia. Imaging the boundary between the downgoing slab and the upper plate along the Calabrian subduction zone is important for assessing the potential of the subduction zone to generate megathrust earthquakes and was the main objective of this study. Here we present and analyze the results from a 380‐km‐long, wide‐angle seismic profile spanning the complete subduction zone, from the deep Ionian Basin and the accretionary wedge to NE Sicily, with additional constraints offered by 3‐D gravity modeling and the analysis of earthquake hypocenters. The velocity model for the wide‐angle seismic profile images thin oceanic crust throughout the basin. The Calabrian backstop extends underneath the accretionary wedge to about 100 km SE of the coast. The seismic model was extended in depth using earthquake hypocenters. The combined results indicate that the slab dip increases abruptly from 2–3° to 60–70° over a distance of ≤50 km underneath the Calabrian backstop. This abrupt steepening is likely related to the rollback geodynamic evolution of the narrow Calabrian slab, which shows great similarity to the shallow and deep geometry of the Gibraltar slab. Plain Language Abstract: We investigate the deep crustal structure of southern Italy and the central Mediterranean where some of the oldest oceanic crust on Earth is actively descending (subducting) into its interior (Speranza et al., 2012). This process causes much of the moderate seismicity observed in this region and may be responsible for strong historical earthquakes as well (Gutscher et al., 2006). Deep seismic data recorded during a marine geophysical expedition performed in 2014 allow us to reconstruct the 3‐D geometry of this subduction zone. Our data reveal a 1–4‐km‐thick evaporitic (salt bearing) layer in the 13‐km‐thick accretionary wedge. The thin underlying crust has characteristics of oceanic crust. The adjacent onshore domains (E Sicily and SW Calabria) are composed of 25–30‐km‐thick crust with velocities typical of continental crust. Together with earthquake travel‐time tomography (providing images of the subducting slab down to 300 km) and gravity modeling, we can for the first time image the abrupt steepening of the subducting slab, the "slab hinge, " where slab dip increases from ≤5° to >60° over a downdip distance of 50 km. This slab dip is steep compared to other subduction zones, for example, in Northern Honshu, Japan, or Sumatra, where the slab dip remains roughly 10°‐ down to 40‐km depth and therefore may have consequences on the seismicity of the region. Key Points: Wide‐angle seismic and 3D gravity modeling image the deep structure of the Calabrian subduction zone The gravity modeling implies that there is no mantle layer between the Calabrian backstop crust and the dipping slab Extension of the model using earthquake hypocenters indicates that the slab dip increases abruptly at the Calabrian backstop